Nitrogen fertilization, fungicide application, and genetic resistance for the management of diseases on wheat - Andrea Román Ramos; Daniel Debona; Eduardo Rodríguez Maldonado; Leandro José Dallanol (Acta Scientiarum. Agronomy, 2025)
Nitrogen (N) fertilization is a common practice to increase grain yield worldwide. This study aimed to determine the effects of three N rates (70, 130, and 200 kg ha−1, referred to as low, recommended, and high, respectively) and a pre-mix fungicide (bixafen + prothioconazole + trifloxystrobin) on the disease intensity and grain yield of 2 early-maturing wheat cultivars named as TBIO Audaz and TBIO Tibagi. Two field experiments were conducted during the 2019 and 2020 growing seasons using the split–split plot design. Tan spot, powdery mildew, leaf rust, and Fusarium head blight (FHB) were the primary diseases observed. The recommended and high N rates reduced the area under the disease progress curve (AUDPC) for tan spot. However, the AUDPC for powdery mildew increased with high N for both cultivars, but N rates did not affect leaf rust or FHB. The use of early maturing wheat cultivars did not prevent the occurrence of FHB damage, except on plants from cultivar TBIO Audaz known to be moderately resistant. When combined with N fertilization, fungicide application reduced the AUDPC for tan spot, powdery mildew, leaf rust, and FHB by 31, 33, 75, and 40%, respectively, compared to the non-treated control. The cultivar × fungicide and cultivar × N interactions were significant (p < 0.05) for AUDPCs and yield variables. Both the recommended and high N rates similarly increased the yield, health area duration, and tan spot control at the same level compared to the low N rate. These findings combined with economic and cost-efficiency analyses suggest that using a moderately resistant cultivar with recommended N rates help to maintain adequate N use efficiency and economic returns to growers.